Information needs, information seeking behaviour and information use behaviour of researchers at the Faculty of Veterinary Science, University of Pretoria and how these needs are being met by the information support delivered by the Jotello F Soga Library - Fourie, Ina (University of Pretoria, 2015)
Dissertation (MIS) -- University of Pretoria, 2015.